deleted 1071 characters in body
Source Link
barlop
  • 281
  • 3
  • 9

Is there a name for the fallacy that refuting an argument refutes the proposition?

e.g. there is a belief in X..

somebody provides an argument for X.. or even a bunch of arguments for X.

Somebody refutes these arguments.

But they commit the fallacy, of thinking that since they have refuted these arguments for the conclusion X, they have thus refuted the proposition and shown ¬X. When really they've only refuted the arguments given for it.

Is there a name for that fallacy?

Added

Ying has mentioned the inverse.. i.e. given a logical expression of an implication (When P happens Q happens) P->Q. That'd be a case of a premise P leading to conclusion Q. So if somebody says P->Q leads to ¬P->¬Q then it'd be a fallacy. Here is a twist though.

What if somebody says that they have refuted all arguments for Q, or found none convincing. Would that mean that they have refuted all possible causes of Q. And therefore, ¬Q?

For example, I understand it to be the case [an earlier edit had something added but that the reason why A->B doesn't mean ¬A->¬B is because there may be some other possible cause of B. e.g. there maything should be made into a C->B as well. Butseparate question so i'll keep this question to what if somebody says they have refuted all possible arguments for B, and they don't think there are any other good arguments. If arguments for a proposition are refuted / if the one existing argument for a proposition is refuted, does that mean that all causes/justifications are now gone and then the proposition is false?

I think not, because arguments are not causes. So if all arguments are refuted, then it won't prove ¬P. It'll just remove justification for belief in P.

But then if arguments aren't causes, is it wrong to say P->Q for an argument and maybe post a conclusion, as if P causes Q?separate different question another time]

Is there a name for the fallacy that refuting an argument refutes the proposition?

e.g. there is a belief in X..

somebody provides an argument for X.. or even a bunch of arguments for X.

Somebody refutes these arguments.

But they commit the fallacy, of thinking that since they have refuted these arguments for the conclusion X, they have thus refuted the proposition and shown ¬X. When really they've only refuted the arguments given for it.

Is there a name for that fallacy?

Added

Ying has mentioned the inverse.. i.e. given a logical expression of an implication (When P happens Q happens) P->Q. That'd be a case of a premise P leading to conclusion Q. So if somebody says P->Q leads to ¬P->¬Q then it'd be a fallacy. Here is a twist though.

What if somebody says that they have refuted all arguments for Q, or found none convincing. Would that mean that they have refuted all possible causes of Q. And therefore, ¬Q?

For example, I understand it to be the case that the reason why A->B doesn't mean ¬A->¬B is because there may be some other possible cause of B. e.g. there may be a C->B as well. But what if somebody says they have refuted all possible arguments for B, and they don't think there are any other good arguments. If arguments for a proposition are refuted / if the one existing argument for a proposition is refuted, does that mean that all causes/justifications are now gone and then the proposition is false?

I think not, because arguments are not causes. So if all arguments are refuted, then it won't prove ¬P. It'll just remove justification for belief in P.

But then if arguments aren't causes, is it wrong to say P->Q for an argument and a conclusion, as if P causes Q?

Is there a name for the fallacy that refuting an argument refutes the proposition?

e.g. there is a belief in X..

somebody provides an argument for X.. or even a bunch of arguments for X.

Somebody refutes these arguments.

But they commit the fallacy, of thinking that since they have refuted these arguments for the conclusion X, they have thus refuted the proposition and shown ¬X. When really they've only refuted the arguments given for it.

Is there a name for that fallacy?

[an earlier edit had something added but that thing should be made into a separate question so i'll keep this question to what it is and maybe post a separate different question another time]

edited title
Source Link
virmaior
  • 24.3k
  • 3
  • 45
  • 104

Is there a name for the fallacy that refuting the argument refutes the propositionconclusion?

Is there a name for the fallacy that refuting an argument refutes the proposition?

e.g. there is a belief in X..

somebody provides an argument for X.. or even a bunch of arguments for X.

Somebody refutes thethese arguments.

But they commit the fallacy, of thinking that since they have refuted thethese arguments for the conclusion X, they have thenthus refuted the proposition and shown ¬X. When really they've only refuted the arguments given for it.

Is there a name for that fallacy?

Added

Ying has mentioned the inverse.. i.e. given a logical expression of an implication (When P happens Q happens) P->Q. That'd be a case of a premise P leading to conclusion Q. So if somebody says P->Q leads to ¬P->¬Q then it'd be a fallacy. Here is a twist though.

What if somebody says that they have refuted all arguments for Q, or found none convincing. Would that mean that they have refuted all possible causes of Q. And therefore, ¬Q?

For example, I understand it to be the case that the reason why A->B doesn't mean ¬A->¬B is because there may be some other possible cause of B. e.g. there may be a C->B as well. But what if somebody says they have refuted all possible arguments for B, and they don't think there are any other good arguments. If arguments for a proposition are refuted / if the one existing argument for a proposition is refuted, does that mean that all causes/justifications are now gone and then the proposition is false?

I think not, because arguments are not causes. So if all arguments are refuted, then it won't prove ¬P. It'll just remove justification for belief in P.

But then if arguments aren't causes, is it wrong to say P->Q for an argument and a conclusion, as if P causes Q?

Is there a name for the fallacy that refuting the argument refutes the proposition?

Is there a name for the fallacy that refuting an argument refutes the proposition?

e.g. there is a belief in X..

somebody provides an argument for X.. or even a bunch of arguments for X.

Somebody refutes the arguments.

But they commit the fallacy, of thinking that since they have refuted the arguments, they have then refuted the proposition and shown ¬X. When really they've only refuted the arguments given for it.

Is there a name for that fallacy?

Added

Ying has mentioned the inverse.. i.e. given a logical expression of an implication (When P happens Q happens) P->Q. That'd be a case of a premise P leading to conclusion Q. So if somebody says P->Q leads to ¬P->¬Q then it'd be a fallacy. Here is a twist though.

What if somebody says that they have refuted all arguments for Q, or found none convincing. Would that mean that they have refuted all possible causes of Q. And therefore, ¬Q?

For example, I understand it to be the case that the reason why A->B doesn't mean ¬A->¬B is because there may be some other possible cause of B. e.g. there may be a C->B as well. But what if somebody says they have refuted all possible arguments for B, and they don't think there are any other good arguments. If arguments for a proposition are refuted / if the one existing argument for a proposition is refuted, does that mean that all causes/justifications are now gone and then the proposition is false?

I think not, because arguments are not causes. So if all arguments are refuted, then it won't prove ¬P. It'll just remove justification for belief in P.

But then if arguments aren't causes, is it wrong to say P->Q for an argument and a conclusion, as if P causes Q?

Is there a name for the fallacy that refuting the argument refutes the conclusion?

Is there a name for the fallacy that refuting an argument refutes the proposition?

e.g. there is a belief in X..

somebody provides an argument for X.. or even a bunch of arguments for X.

Somebody refutes these arguments.

But they commit the fallacy, of thinking that since they have refuted these arguments for the conclusion X, they have thus refuted the proposition and shown ¬X. When really they've only refuted the arguments given for it.

Is there a name for that fallacy?

Added

Ying has mentioned the inverse.. i.e. given a logical expression of an implication (When P happens Q happens) P->Q. That'd be a case of a premise P leading to conclusion Q. So if somebody says P->Q leads to ¬P->¬Q then it'd be a fallacy. Here is a twist though.

What if somebody says that they have refuted all arguments for Q, or found none convincing. Would that mean that they have refuted all possible causes of Q. And therefore, ¬Q?

For example, I understand it to be the case that the reason why A->B doesn't mean ¬A->¬B is because there may be some other possible cause of B. e.g. there may be a C->B as well. But what if somebody says they have refuted all possible arguments for B, and they don't think there are any other good arguments. If arguments for a proposition are refuted / if the one existing argument for a proposition is refuted, does that mean that all causes/justifications are now gone and then the proposition is false?

I think not, because arguments are not causes. So if all arguments are refuted, then it won't prove ¬P. It'll just remove justification for belief in P.

But then if arguments aren't causes, is it wrong to say P->Q for an argument and a conclusion, as if P causes Q?

Tweeted twitter.com/StackPhilosophy/status/854120382571401216
added 1266 characters in body
Source Link
barlop
  • 281
  • 3
  • 9

Is there a name for the fallacy that refuting an argument refutes the proposition?

e.g. there is a belief in X..

somebody provides an argument for X.. or even a bunch of arguments for X.

Somebody refutes the arguments.

But they commit the fallacy, of thinking that since they have refuted the arguments, they have then refuted the proposition and shown ¬X. When really they've only refuted the arguments given for it.

Is there a name for that fallacy?

Added

Ying has mentioned the inverse.. i.e. given a logical expression of an implication (When P happens Q happens) P->Q. That'd be a case of a premise P leading to conclusion Q. So if somebody says P->Q leads to ¬P->¬Q then it'd be a fallacy. Here is a twist though.

What if somebody says that they have refuted all arguments for Q, or found none convincing. Would that mean that they have refuted all possible causes of Q. And therefore, ¬Q?

For example, I understand it to be the case that the reason why A->B doesn't mean ¬A->¬B is because there may be some other possible cause of B. e.g. there may be a C->B as well. But what if somebody says they have refuted all possible arguments for B, and they don't think there are any other good arguments. If arguments for a proposition are refuted / if the one existing argument for a proposition is refuted, does that mean that all causes/justifications are now gone and then the proposition is false?

I think not, because arguments are not causes. So if all arguments are refuted, then it won't prove ¬P. It'll just remove justification for belief in P.

But then if arguments aren't causes, is it wrong to say P->Q for an argument and a conclusion, as if P causes Q?

Is there a name for the fallacy that refuting an argument refutes the proposition?

e.g. there is a belief in X..

somebody provides an argument for X.. or even a bunch of arguments for X.

Somebody refutes the arguments.

But they commit the fallacy, of thinking that since they have refuted the arguments, they have then refuted the proposition and shown ¬X. When really they've only refuted the arguments given for it.

Is there a name for that fallacy?

Is there a name for the fallacy that refuting an argument refutes the proposition?

e.g. there is a belief in X..

somebody provides an argument for X.. or even a bunch of arguments for X.

Somebody refutes the arguments.

But they commit the fallacy, of thinking that since they have refuted the arguments, they have then refuted the proposition and shown ¬X. When really they've only refuted the arguments given for it.

Is there a name for that fallacy?

Added

Ying has mentioned the inverse.. i.e. given a logical expression of an implication (When P happens Q happens) P->Q. That'd be a case of a premise P leading to conclusion Q. So if somebody says P->Q leads to ¬P->¬Q then it'd be a fallacy. Here is a twist though.

What if somebody says that they have refuted all arguments for Q, or found none convincing. Would that mean that they have refuted all possible causes of Q. And therefore, ¬Q?

For example, I understand it to be the case that the reason why A->B doesn't mean ¬A->¬B is because there may be some other possible cause of B. e.g. there may be a C->B as well. But what if somebody says they have refuted all possible arguments for B, and they don't think there are any other good arguments. If arguments for a proposition are refuted / if the one existing argument for a proposition is refuted, does that mean that all causes/justifications are now gone and then the proposition is false?

I think not, because arguments are not causes. So if all arguments are refuted, then it won't prove ¬P. It'll just remove justification for belief in P.

But then if arguments aren't causes, is it wrong to say P->Q for an argument and a conclusion, as if P causes Q?

Source Link
barlop
  • 281
  • 3
  • 9
Loading